If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2 + 15x) = 0 (2 * 6 + 15x * 6) = 0 (12 + 90x) = 0 Solving 12 + 90x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 90x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 90x = 0 + -12 90x = 0 + -12 Combine like terms: 0 + -12 = -12 90x = -12 Divide each side by '90'. x = -0.1333333333 Simplifying x = -0.1333333333
| 2/7-1/14 | | 32b-4+-2b-1= | | 10+5r=10-r | | (2/x)-x=(-23/5) | | (7/8)/m=(1/7) | | =(2a+3b-4c) | | 4+5-2=33 | | -2y+6+9y= | | 2/3-1/x=5/3x | | 3(n-4)=-15 | | X*.38=112 | | 26x^2-130x+6=0 | | 4x^2-y^2=11 | | 14j+3k= | | X^2+x+1=2 | | 8x+2z=4+7y | | 5x+2.5y=840 | | 7p-10=-3p+5 | | 10p+5=5p-5 | | 12y+8=13y-18 | | 20-2x=x+8 | | x^2-10=350 | | 17=9y-5y-3 | | yl=14j+3k | | 11=-9x+5x | | 324÷1/8 | | 16N=2(N+12)+2N | | 5x+5=6y | | 7(x-9)=14 | | 2x+(5x-3y)= | | 16N=(N+12)+2N | | -1.8=.4x |